Analisis Tingkat Self-Esteem Siswa Kelas XI MAS As-Salam Naga Beralih Pada Pembelajaran Matematika - Nada, Atika Nahda; Depriwana Rahmi; Annisah Kurniati; Suci Yuniati (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
This study aims to describe the level of self-esteem of class XI students of MAS As-Salam Naga Beralih. Theresearch method used is a descriptive method with a quantitative approach with a total of 15 subjects. The instrument used in this study is a non-test instrument in the form of a self-esteem questionnaire with 30 statements that have been tested by 3 expert validators. The data analysis technique is carried out descriptively, namely by explaining the meaning contained in the numbers in cach questionnaire statement that has been filled in by students, and determining the students' self-esteem category. Based on the results of the analysis of each statement that has been distributed to students on each indicator, it results that the level of self-esteem of students in class XI MAS As-Salam Naga Beralih is generally in the medium category with a percentage of 67%, high category 20%, and low category 13%. With the data obtained, it can be concluded that the level of self-esteem of students in grade XI MAS As-Salam Naga Beralih has a moderate level of self-esteem.